Implementasi Metode SMART Menentukan Penerima Beasiswa Bidikmisi Pada SMA Negri 2 Moro’o Kabupaten Nias Barat - Rizkiman Waruru; Ade Zulkarnain Hasibuan; Tommy (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
The Bidikmisi Scholarship is an education fee assistance program for prospective students who are economically disadvantaged and have good academic potential to study at university until they graduate on time. SMA Negeri 2 Moro'o West Nias Regency is one of the schools that runs the Bidikmisi scholarship program, the selection process takes three weeks to one month, with the selection process taking up to one month of course this is less efficient. Apart from that, it is feared that the resulting assessment will be subjective, where the assessment is based on personal interests, causing the scholarship to not be on target. The aim of this research is to build a decision support system to determine Bidikmisi scholarship recipients using the Microsoft Visual Basic programming language with the SMART ( Simple Multi Attribute Rating Technique ) method. at SMA Negeri 2 Moro'o, West Nias Regency. The system that has been designed using the Microsoft Visual Basic programming language can provide more precise information, because it uses the SMART ( Simple Multi Attribute Rating Technique ) method, so there is no longer any doubt in making a decision. It is hoped that the designed application will make it easier for SMA Negeri 2 Moro'o West Nias Regency to determine Bidikmisi scholarship acceptance